2018
DOI: 10.15171/mejdd.2018.104
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Look at Irritable Bowel Syndrome and its Associated Factors Considering the Rome IV Criteria: A Penalized Smoothly Clipped Absolute Deviation Regression Approach in the Pars Cohort Study

Abstract: BACKGROUND After the introduction of the Rome IV criteria for the diagnosis of irritable bowel syndrome (IBS), studies on the clinical significance of the new criteria in the settings of a large study has been scarce. Objective: Herein we used the infrastructures provided by one the largest cohort studies in Iran to evaluate the epidemiological features related to IBS. METHODS A total of 9264 participants, were enrolled in the initial registry. Diagnosis of IBS was done using the Rome IV criteria. Individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(45 reference statements)
3
8
0
Order By: Relevance
“…The prevalence of IBS was numerically higher in the unmarried population than in their married counterparts. This finding is consistent with the results of other studies,[ 1 38 39 40 ] although our findings did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of IBS was numerically higher in the unmarried population than in their married counterparts. This finding is consistent with the results of other studies,[ 1 38 39 40 ] although our findings did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 89%
“…According to some studies,[ 38 40 ] IBS has an inverse relationship with education. Contrary to this, we observed the opposite and our results found the educational level to be an important contributor for IBS.…”
Section: Discussionmentioning
confidence: 99%
“…IBS was found to be more common in unmarried people than in their married counterparts. Despite the fact that our results did not have statistical significance, they are consistent with those of other treatises [1,38,39,40]. IBS has a converse relevance with instruction, according to several treatises [38,40] (education).…”
Section: Discussionsupporting
confidence: 76%
“…25 In contrast (and consistent with our findings), one study found that being married is a risk factor in patients with irritable bowel syndrome. 26 We suggest that in the present study, the effect of marital status was confounded by age: single employees were young and had few life burdens.…”
Section: Discussionmentioning
confidence: 63%